2022
DOI: 10.3847/1538-4357/ac9790
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Limits of AGN Feedback and the Onset of Thermal Instability in the Most Rapidly Star-forming Brightest Cluster Galaxies

Abstract: We present new, deep, narrow- and broadband Hubble Space Telescope observations of seven of the most star-forming brightest cluster galaxies (BCGs). Continuum-subtracted [OII] maps reveal the detailed, complex structure of warm (T ∼ 104 K) ionized gas filaments in these BCGs, allowing us to measure spatially resolved star formation rates (SFRs) of ∼60–600 M ⊙yr−1. We compare the SFRs in these systems and others from the literature to their intracluster medium cooling rates ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 144 publications
1
13
0
Order By: Relevance
“…In this context, Cavagnolo et al (2011) noted filamentary structures in the residual optical image of the BCG extending 8-10 kpc southward. These structures were recently confirmed by Calzadilla et al (2022), who produced continuum-subtracted [O II] maps of nebular emission using the Hubble Space Telescope. The overlay of [O II] contours on the t cool /t ff map (see lower right panel in Figure 5) reveals that cool gas at ∼10 4 keV is coincident with the region where the minimum in t cool /t ff is found (within ∼20 kpc S from the center).…”
Section: Thermodynamic Maps Of the Icmmentioning
confidence: 60%
See 3 more Smart Citations
“…In this context, Cavagnolo et al (2011) noted filamentary structures in the residual optical image of the BCG extending 8-10 kpc southward. These structures were recently confirmed by Calzadilla et al (2022), who produced continuum-subtracted [O II] maps of nebular emission using the Hubble Space Telescope. The overlay of [O II] contours on the t cool /t ff map (see lower right panel in Figure 5) reveals that cool gas at ∼10 4 keV is coincident with the region where the minimum in t cool /t ff is found (within ∼20 kpc S from the center).…”
Section: Thermodynamic Maps Of the Icmmentioning
confidence: 60%
“…The low-entropy (30 keV cm 2 ) and short cooling time (t cool 1 Gyr) ICM is preferentially found between and behind the X-ray cavities, which may indicate that the bubbles are stimulating cooling. In this context, the region with the shortest cooling time (∼440 Myr) and minimum t cool /t ff ratio (∼18) is located within 20 kpc S of the center, where filamentary patches of [O II] nebular emission tracing star-forming gas were recently detected (Calzadilla et al 2022). 3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latest gain and charge transfer inefficiency corrections were applied, with improved background screening for the VFAINT telemetry mode. Modeling of the global ICM properties was done as in Calzadilla et al (2022), and the thermodynamic profiles are shown and discussed in Section 3.1.…”
Section: X-ray (Chandra)mentioning
confidence: 99%